A case study on the difference between students of SPM and O-level backgrounds in studying mathematics in the A-level programme - Moy, Tow Yoon *; Lee, Jeanie Shu Shean *; Wong, Sock Leng *; Yong, Yau * (2019)
This study aims to understand the difference in the perceived and actual mathematics performance of the A-Level students from the SPM and O-Level backgrounds. Perceptions and expectations of lecturers are explored using an open-ended questionnaire. A comprehensive survey to understand the students’ attitude, proficiency in the English language and other important predictors of academic achievement is also conducted. Content analysis is used to analyse the lecturers’ feedback. Descriptive statistics, parametric and non-parametric tests are conducted to test differences between the two cohorts.